2017
DOI: 10.1002/esp.4103
|View full text |Cite
|
Sign up to set email alerts
|

Shift from transport limited to supply limited sediment concentrations with the progression of monsoon rains in the Upper Blue Nile Basin

Abstract: Long‐term erosion monitoring data in the Ethiopian highlands are only available from the Soil Conservation Research Program (SCRP) watersheds including the Anjeni watershed. The 113 ha Anjeni watershed was established in 1984 and fanya juu terraces were installed in 1986. Runoff and erosion data are available from three different plot sizes and at the watershed outlet. The objective of this study was to investigate how erosion processes and sediment rating parameters vary with plot size and the progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…In most watersheds, sediment concentrations are elevated in the beginning of the rain phase after the soils are plowed and rills form [22,23,28,[44][45][46][47]. Once the rills have formed, sediment concentrations decrease.…”
Section: Overall Impact Of Soil and Water Conservation On Hydrologicamentioning
confidence: 99%
See 1 more Smart Citation
“…In most watersheds, sediment concentrations are elevated in the beginning of the rain phase after the soils are plowed and rills form [22,23,28,[44][45][46][47]. Once the rills have formed, sediment concentrations decrease.…”
Section: Overall Impact Of Soil and Water Conservation On Hydrologicamentioning
confidence: 99%
“…To discuss the differences in discharge and runoff coefficients between the two watersheds, we note that prior experimental studies have found that the main runoff generation mechanism in the (sub) humid Ethiopian highlands is saturation excess runoff [15,20,22,24,[45][46][47][48]. Saturated excess overland flow occurs at locations either where the soils become saturated above an impeding layer or where the regional groundwater reaches the surface.…”
Section: Dischargementioning
confidence: 99%
“…After gullies are rehabilitated erosion rates decrease rapidly (Akale et al ., ). In addition, high erosion rates of up to 125 Mg ha ‐1 yr ‐1 have been reported for plot studies (Mitiku et al ., ; Bewket and Teferi, ); but these large losses are moderated by the time the water reaches the outlet (Bayabil et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Previous hydrological studies in the sub-humid and humid Ethiopian highlands have found that the median infiltration rate in the volcanic surface soils is frequently exceeded. Saturation excess overland land flow is therefore common (Liu et al, 2008;Steenhuis et al, 2009;Tilahun et al, 2013Tilahun et al, , 2015Bayabil et al, 2010Bayabil et al, , 2016Bayabil et al, , 2017. This phenomenon is sometimes labeled infiltration excess when the limited infiltrability of the subsurface is the main defining characteristic (Bewket and Sterk, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, despite the implementation of government-imposed water conservation practices, the land has become more degraded in humid and subhumid highlands [26,61], and sediment concentrations in streams have been increasing [62,63]. Annual soil losses equivalent to 1-8 mm per year are not uncommon in small watersheds, with the upper end of the sediment losses being from watersheds that have active gully formations [64,65]. Restoring natural resource bases before soils are fully degraded is important because the harm caused in one year cannot be repaired in a human lifetime [66].…”
Section: Introductionmentioning
confidence: 99%